In Vitro Induction and Identification of Polyploid Amorphophallus muelleri Blume Plants by Colchicine Treatment - Wahyu Widoretno; Rodliyati Azriningsih; Deden Sukmadjaja; Mufidatur Rosyidah (AGRIVITA, Journal of Agricultural Science, 2023)
This research aimed to induce in vitro and identify polyploidy plantlets of Porang (Amorphophallus muelleri Blume) after colchicine treatment. In vitro shoot base explants of porang were cultured on MS medium containing different colchicine concentrations of 30, 60, 90, and 120 mg/l for four weeks while the control was medium without colchicine. After four weeks, all treated and untreated explants were multiplied and regenerated into plantlets. Flow cytometry and chromosome count were employed to determine the plantlet’s ploidy level and chromosome number, respectively. The result showed that colchicine inhibited explant growth, shoot formation, and plantlet regeneration. Increasing colchicine concentration reduces the capacity of explant in shoot formation, the number of shoots and plantlet regeneration. Of 19 plantlets regenerated from colchicine-treated explants, nine plantlets were mixoploid. Percentage of mixoploid plantlet regenerated from treated explant with 30 mg/l colchicine was higher than 60 mg/l colchicine. Mixoploid plants are mixed diploid, tetraploid, and octoploid cells. Chromosome count confirmed that the diploid cell of A. muelleri has 26 chromosomes and a colchicine-induced triploid and tetraploid cell has 39 and 54 chromosomes, respectively.